Eksplorasi Penggunaan Permainan Edukatif Islami Dalam Memahami Konsep Matematika Dasar - Mia Audina Musyadad; Agus Jaenal; Irena Laras; Diah Widiawati; Saepudin Saepudin (Journal on Education, 2024)
Education based on religious values ​​is very important in forming students' character. In this context, the use of Islamic educational games as a basic mathematics learning method in elementary schools has great potential to increase students' understanding, while instilling Islamic values. The aim of this research is to explore the impact of using Islamic educational games in helping students understand basic mathematical concepts at SDIT Kasih Ibu. This research uses a quantitative approach with a pretest-posttest experimental design. Data was collected through pretest and posttest to measure students' mathematical understanding, observations during learning, as well as interviews with teachers and students. The research subjects were 30 fourth grade students who took part in mathematics learning using Islamic educational games. The research results showed a significant increase in understanding basic mathematics after using Islamic educational games. The students' average score on the posttest increased 20 points compared to the pretest. Additionally, students demonstrated higher engagement and increased motivation during learning. This game also supports student character development by integrating Islamic values ​​such as honesty and discipline. Implications: This research suggests that Islamic educational games should be integrated more widely in basic mathematics learning as an effective alternative for improving students' academic understanding and character building in religious-based elementary schools.